Avant-garde art in Ukraine, 1910-1930 : contested memory - Shkandrij, Myroslav, 1950- (Academic Studies Press, 2019)
From pre-war years in Paris to the end of the 1920s in Kyiv, Ukrainians or artists from Ukraine produced some of the world's greatest avant-garde art and made major contributions to painting, sculpture, theatre, and film-making. This book tells their story and explores the roots of their inspiration.